IMPLEMENTASI MODEL CIBEST DALAM MENGUKUR TINGKAT KESEJAHTERAAN PENGRAJIN BATIK DI DESA MONTOR KEC.BANYUATES KAB.SAMPANG - Mauhibbatus Syakirin (LPPM STAI Muhammadiyah Probolinggo, 2025)
Welfare is a condition in which basic needs are fulfilled, encompassing a sense of security, safety, peace, and prosperity. The CIBEST Welfare Model is one of the measurement tools for welfare and poverty from an Islamic perspective. This model consists of four CIBEST quadrants and encompasses indicators of welfare, material deprivation, spiritual deprivation, and absolute poverty. This study seeks to assess the welfare level of batik artisans in Montor Village by employing the CIBEST model. Furthermore, the study seeks to assess the overall welfare level of the Montor Village community through the CIBEST model. The study utilizes a quantitative method. Based on the analysis of 25 samples, it was found that the welfare level of the Montor Village community is divided into several CIBEST quadrants. In Quadrant I (prosperous), there are 14 households, while in Quadrant II (material poverty), there are 11 households. No households were found in Quadrant III (spiritual deprivation) or Quadrant IV (complete/absolute deprivation).